Trade policies in Brazil - Helson C. Braga; William G. Tyler (Institute for Applied Economic Research (ipea), 2015)
This paper provides a descriptive assessment of Brazilian trade policies, with emphasis on the import regime. Import policies in Brazil during the post-war period have consisted basically of the use of tariff and non-tariff barriers to restrict external competition and, in doing so, promote the installation of an ample and diversified industrial sector. As a result of high levels of domestic protection, low levels of competitive pressures, and limited size of the domestic market, the country presents a highly concentraded industrial structure with low levels of productivity efficiency. To improve efficiency is the main challenge for the future of trade policies.
Keywords: 330